Maqashid Based Quránic Interpretation: An Inclusive Approach for the Millenial Generation - Said, Hasani Ahmad; Mukri, Moh; Anggriani, Jum; Wakhid, Ali Abdul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This study develops a maqashid-based inclusive Qur'anic interpretation framework specifically designed for the millennial generation, addressing the significant decline in Qur'anic literacy among young Muslims. The research employs a qualitative approach utilizing library research methodology, integrating hermeneutic analysis, content analysis, and comparative analysis to examine classical maqashid literature and contemporary interpretation challenges. The maqashid al-shariah approach, emphasizing the five essential objectives of preserving religion, life, intellect, lineage, and wealth, provides the theoretical foundation for developing interpretation methods that are both theologically authentic and contextually relevant. The mashlahah (public interest) framework serves as the primary evaluative mechanism for assessing the effectiveness and appropriateness of contemporary interpretation approaches. Results demonstrate successful integration of classical Islamic principles with millennial learning preferences, addressing challenges including digital misinformation, psychological compatibility, gender inclusivity, and cultural diversity. The framework provides systematic solutions for quality control in digital Islamic education, algorithmic bias mitigation, and the development of engaging yet scholarly interpretation content. Implementation guidelines offer practical approaches for educators and institutions to adopt maqashid-based interpretation methods effectively. The study confirms that Islamic teachings remain suitable for all times and places (al-Islam shalih li kulli zaman wa al-makan), demonstrating how Qur'anic interpretation can evolve methodologically while preserving essential principles. This research contributes significantly to Islamic educational theory, providing innovative approaches that maintain scholarly rigor while addressing contemporary generational needs and challenges.